Peningkatan Pengetahuan Siswi Tentang Anemia Setelah Mendapatkan Pendidikan Gizi Dengan Media Video Animasi - Cahyono, Surastomo Budi, Siti Zulaekah, A., M.Si, Ruli Sudaryanto, SST.GZ (2015)
Background : Various ways can be done in the prevention and control of anemia, one of them is by providing good nutrition education with lectures and using the media. Video animation is an effective method of providing such information. Objective : This study aims to determine the effectiveness of the use of video media to increase nutrition knowledge in adolescent females. Research Metods : This research uses Quasy Experiment with pretest posttest control group. The study us 62 samples were divided into two: group lectures method and group video media method. Data includes the value of pretest and posttest. Analysis data used Pired Samples Test, Wilcoxon Signed Rank Test, Mann Whitney Test, Independent Sample Test. Results : The mean pretest group of videos and lectures are 63.73 and 63.97. Posttest mean value of video and lecture group was 73.51 and 73.54. There is significant increase in nutritional knowledge before and after the intervention in both lecture and video group. However, there is no significant difference in the improvement of knowledge between lectures and video group. Conclusion : Nutrition education using the media of video animations can improve the nutritional knowledge in adolscent females.